Experimental study of temperatures during drilling of ex-vivo bovine bones - Fernandes, M.G.A. (2016)
The thermal bone necrosis induced during a drilling process is a frequent and potential phenomenon, which contributes to post-operative problems. The frictional heat generated from the contact between the drill bit and the hole wall is unavoidable. However, understanding advanced techniques for acquiring reliable thermal data on bone drilling is important to ensure the quality of the drilled hole. The purpose of this study is to present two different experimental methods to analyse the drilling conditions that generate the lower temperatures, avoiding the occurrence of thermal bone necrosis. Ex-vivo bovine bones were used to simulate the drilling process considering the effect of drill bit diameter, drill speed and feed-rate. Different experiments were performed to assess the repeatability of the tests. The results identified the drill bit diameter as the most critical parameter for inducing higher temperatures in bone drilling.